Crystallization behaviour of Zr50Cu40Al10 metallic glass with different relaxed state - Pajor, K.; Majka, M.; Błyskun, P.; Gondek, Ł.; Kozieł, T. (Archives of Metallurgy and Materials, 2026)
Zr50Cu40Al10 glass-forming alloy was synthesized at different cooling rates conditions, ranging from 101 to 107 K s–1, to investigate how structural relaxation affects crystallization behaviour and processing stability. XRD confirmed that rapid solidification suppresses crystallization, while DSC revealed supercooled liquid regions. Activation energies obtained by Kissinger and Ozawa analyses increased with cooling rate, reflecting the dominant role of structural disorder induced by high cooling rate delays nucleation via increasing atomic rearrangement cost. These findings clarify the kinetic-thermodynamic balance controlling crystallization and provide guidelines for tailoring Zr-based metallic glasses for thermoplastic forming and controlled nanocrystallization applications.